EZH2, a unique marker of malignancy in effusion cytology. Issue 2 (2nd May 2013) - Jiang, Huimiao; Gupta, Raavi; Somma, Jonathan
<x xml:space="preserve">Abstract</x> Distinguishing reactive mesothelial cells from metastatic disease, typically adenocarcinoma, in effusion cytology can be challenging at times. We currently use a panel of immunocytochemical markers for select cases including MOC‐31 and BerEp4, but difficulties still exist. Enhancer of zeste homologue 2 (EZH2) plays important roles in epigenetic silencing and cell cycle regulation and is upregulated in a wide variety of malignancies. Thus, we hypothesized that EZH2 immunocytochemistry, which to our knowledge has not yet been reported on cytology material, might serve as a unique marker of malignancy in morphologically equivocal effusion specimens by highlighting aberrant protein expression in malignant cells. A total of 96 (48 benign and 48 malignant) effusion cases were selected retrospectively from our department archives. All malignant cases were metastatic adenocarcinomas except for three high grade neuroendocrine carcinomas (two lungs and one ovary), one cervical squamous cell carcinoma, and one epithelioid endometrial stromal sarcoma. The 48 benign cases were all negative for EZH2, and 43 of 48 malignant effusions were positive. As a solitary marker, EZH2 exhibited a sensitivity of 90% and a specificity of 100% (P < 0.0001). EZH2 functioned as a unique and accurate marker of malignancy in this series of effusions. Relative to published data, EZH2 demonstrated a sensitivity comparable to MOC‐31 and superior to BerEp4, and a specificity superior to both of these commonly used immunostains. Thus, EZH2 is likely to be of great value as an adjunct to morphology in diagnosing malignancy in effusion specimens. Diagn. Cytopathol. 2014;42: 111–116. © 2013 Wiley Periodicals, Inc.